Scalable coupled aquaponics design: Lettuce and tilapia production using a parallel unit process approach - Tetreault, Joseph; Fogle, Rachel L.; Guerdat, Todd (Frontiers in Sustainable Food Systems, 2023)
Coupled aquaponics is the integration of recirculating aquaculture systems (RAS) with hydroponic cropping systems (HCS) into a single system with shared water treatment units. Potential benefits of integration include water conservation, reduced reliance on finite mineral fertilizers, and intensive year-round location-independent production of lean proteins and fresh vegetables. However, coupled aquaponic practitioners have found minimal commercial success to date. This has been mostly due to the use of system designs which are not based on contemporary water treatment principles, especially those for commercial aquaculture. Instead, conventional coupled aquaponic system design has been based on a linear framework assuming fish wastes are readily utilized as plant fertilizers, with minimal emphasis on waste treatment or individual component hydraulic retention times. The result has been economic failures due to misbalancing the cost of inputs, the value of the outputs, and the time required to reach a marketable harvest size for both crops: fish and plants. This manuscript provides theoretical calculations based on existing standards in commercial RAS and HCS for sizing plant, fish, and biofiltration units focused on nitrogenous waste production from fish. Successful integration of HCS and RAS is defined as achieving industry standard production timelines for lettuce (seed to harvest time of 35 days) and Nile tilapia (fry to a 624 g average harvest weight in 35 weeks). Equations and examples to calculate lettuce yield, daily lettuce nitrogen requirement, fish feed rates to achieve specific nitrogen production rates, and fish tank and biofilter volumes are provided.